Chinese medicinal formula, Qinggan Huoxue Recipe protects rats from alcoholic liver disease via the lipopolysaccharide-Kupffer cell signal conduction pathway - WU, TAO (D.A. Spandidos, 2014)
The Chinese medicinal formula, Qinggan (QG) Huoxue (HX) Recipe (R) exerts a range of pharmacological effects, including reversible steatosis, decreased levels of inflammatory cytokines and lipid peroxidation resistance. The aim of the present study was to determine the specific mechanisms of QGHXR hepatoprotection through the lipopolysaccharide-Kupffer cell (LPS-KC) signal conduction pathway in rats with alcoholic liver disease (ALD). ALD rats were exposed to the compound factors, QGR and HXR. Hematoxylin and eosin staining was conducted to evaluate the pathological changes in the liver following QGHXR treatment and an enzyme-linked immunosorbent assay was performed to measure the content of tumor necrosis factor (TNF)-α in the plasma. Immunohistochemical staining was conducted to examine the expression of cell differentiation antigen (CD) 68 and 14. In addition, western blot analysis and reverse transcription-polymerase chain reaction were used to measure the expression of Toll-like receptor 4 (TLR(4)), phosphorylated-extracellular regulated protein kinases (p-ERK), nuclear factor (NF)-κB, CD14 and TNF-α. Following stimulation with the compound factors, the rats exhibited increased alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels, as well as marked pathological changes. Furthermore, the related molecules in the LPS-KC pathway were upregulated and QGHXR was identified to be effective in the LPS-KC signal conduction pathway in the ALD rats. QGHXR was superior to QGR and HXR in reducing the serum ALT and AST levels, regulating CD14, TLR(4), NF-κB, ERK and TNF-α as well as improving the pathological changes. The results indicated that QGHXR therapy may provide a novel strategy for treating ALD via regulation of the related molecules in the LPS-KC signaling pathway.